All dressed in white : an under suspicion novel - Clark, Mary Higgins; Burke, Alafair (2015)
"The second thrilling novel in the New York Times bestselling Under Suspicion series following The Cinderella Murder, featuring intrepid television producer Laurie Moran as she investigates the case of a missing bride. Five years ago Amanda Pierce was excitedly preparing to marry her college sweetheart in a lavish ceremony at The Grand Victoria Hotel in Palm Beach. Then, with their guests and families on site, Amanda disappeared. In present-day New York City, Laurie Moran realizes a missing bride is the perfect cold case for her investigative television series, Under Suspicion. She and her team set out to recreate the night of the disappearance at the Florida resort with Amanda's friends and family in attendance, hoping to shed new light on the mystery as the series has done in past episodes. With a jealous sister, playboy groomsmen, Amanda's former fiance; now married to a bridesmaid, and rumors about the "beloved" bride herself, Laurie and Under Suspicion host Alex Buckley quickly realize everyone has a theory about why Amanda vanished into thin air. One thing is certain: whoever was behind Amanda's disappearance plans to keep the truth hidden "until death do they part..." The bestselling Under Suspicion series from Mary Higgins Clark and Alafair Burke offers "plenty of intrigue and excitement" (Publishers Weekly, on The Cinderella Murder). Featuring the chilling suspense and elegant settings readers have come to love, All Dressed in White is not to be missed"--
Keywords: Television programs -- Fiction; Television personalities -- Fiction; Missing persons -- Investigation -- Fiction; Cold cases (Criminal investigation) -- Fiction; FICTION / Suspense; FICTION / Mystery & Detective / General; FICTION / Thrillers; Suspense fiction; Mystery fiction